Geology, mineralogy, ore paragenesis, and molybdenite Re-Os geochronology of Sn-W (-Mo) mineralization in Padatgyaung and Dawei, Myanmar: Implications for timing of mineralization and tectonic setting. (1st June 2021) - Myint, Aung Zaw; Li, Huan; Mitchell, Andrew; Selby, David; Wagner, Thomas
Graphical abstract: Highlights: Magmatic-hydrothermal activity occurred as several discrete events in the Western Granite Province of SE Asia. The Sn-W (-Mo) mineralization constrained to Cretaceous to Paleocene age. Extensive granite-associated Sn-W (-Mo) mineralization events in the Western Granite Province occurred during ca. 75 Ma and 60 Ma. Abstract: The Sn-W (-Mo) deposits of Myanmar are mostly located in the Western Granite Province that is well known for its world-class Sn-W (-Mo) deposits. Previous studies have constrained the age of the granitic intrusions of the province and the timing of mineralization for a few deposits, but most of the mineralization ages are not well established. In this study, new molybdenite Re-Os dating of two Sn-W-(Mo) regions, Padatgyaung and Dawei, together with their geological setting and mineral paragenesis are carried out to constrain the timing of ore formation and geodynamic setting. In the Padatgyaung region, two weighted average Re-Os model ages of 64.23 ± 0.29 Ma (MSWD = 0.49, 2σ) and of 60.54 ± 0.45 Ma (MSWD = 1.3, 2σ) from vein molybdenites are considerably younger than molybdenite from tin mineralized greisen which has a weighted Re-Os model age of 68.5 ± 2.7 Ma (MSWD = 0.14, 2σ). This demonstrates that the vein-type W-Mo mineralization formed after tin mineralized greisenization. Combining our new age data with previous geochronological data, the Re-Os model age of 63.09 ± 0.17 Ma from the Wagone quartz vein suggests that the Sn-W(-Mo) mineralization in the Dawei region took place at around 70–60 Ma (Late Cretaceous to Paleocene). This study indicates the presence of a significant and discrete granite-related Sn-W(-Mo) mineralization with an age of 75–60 Ma in the Western Granite Province, although the overall age range of Sn-W mineralization in the belt spans from 120 to around 40 Ma emplaced during normal subduction and roll-back of the Neo-Tethyan oceanic crust.